The Effect of Compost, Cow, and Goat Manure on Inceptisols Soil Characteristics From Smallholder Plantation, Karangploso District, Malang Regency - Soemarno; Pramesti, Gitri Ardia; Putrideny, Ayesha Ammara; Ifadah, Nisfi Fariatul (Directorate of Research and Community Services, 2024)
Inceptisol soils mainly have medium to high physical properties. However, these physical properties can be degraded if there is a limiting factor in the terrain, which is the degree of slope and low SOC. On steep slopes, soil infiltration rates decrease, which leads to the limited available soil moisture in root zone subsoil. Application of compost or manure into the soil can improve soil physical properties and increase the soil organic carbon (SOC), it improves soil porosity and improve available water capacity (AWC). This study used the factorial completely randomized design with 8 treatments and 4 replications. The treatments included (Control + Topsoil), (Control + Subsoil), (Compost + Topsoil), (Compost + Subsoil), (Cow manure + Topsoil), (Cow manure + Subsoil), (Goat manure + Topsoil), (Goat manure + Subsoil). The results showed that (1) the addition of compost and manure can improve the physical properties of topsoil and subsoil, reducing macro porosity, increasing meso and microporosity, and increasing field capacity. (2) The addition of compost and manure can increase the water holding capacity of topsoil by 36.72% at 1 MAI to 41.12% at 5 MAI and inceptisol subsoil by 35.27% at 1 MAI to 36.42% at 5 MAI. (3) The addition of compost and manure can increase the C-organic content of topsoil by 1.62% at 1 MAI to 1.72% at 5 MAI and subsoil by 1.24% at 1 MAI to 1.38% at 5 MAI.